The Market Perception of Tourism Destination for Chinese Promotion in Chiang Rai, Thailand - YUAN MIN; ZHANG SHUHUA; SUN FUYUAN (Fa Nuea Journal, 2022)
There are rich natural scenery resources, mountain ethnic tourism, humanities and arts resources in Chiang Rai, Thailand; but they are not known to the most Chinese travelers through the design of survey questionnaires, and from the Chinese travelers’ perception of Chiang Rai’s tourist destinations. We learned more about the tourism needs of Chinese travelers in Chiang Rai, the research result showed the success factors of tourism destinations. The unearthed four types of tourism destinations with obvious characteristics of Chiang Rai to experience for potential Chinese tourists. We learned about the ways and forms of tourist destinations from the Chinese. We will deeply explore the unique tourism resources of Chiang Rai, and propose corresponding promotion strategies to enhance the taste of local tourism resources, attract more potential tourists to promote local economic development.